(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
At the beginning of the twentieth century, many forces that influenced the architectural space on the material and intellectual levels, where concepts and ideas that tried to address the problem of rapid development in these forces emerged.These concepts and fluidity, which is characteristic of modern architectural space to accommodate any sudden change For any power that affects it, be it social, economic, political, environmental, material, philosophical, etc.hence the research problem emerged «in the lack of clarity of the concept of fluidity in social sciences and its impact on contemporary architectural space».The study aims to explain how social fluidity affected the contemporary space component and its tendency towards fluidity in form and performance.The research followed the analytical approach in tracking the concept of liquidity in physics and social thought to crystallize this concept in contemporary architectural thought, and then analysis of some contemporary architectural models, according to the indicators that emerged from the theoretical framework.The research concluded that the fluidity in social sciences contributed to making modern architectural space behave in two types: First, formal behavior through formal and spatial flow .Second, interactive behavior through relationships like user-with-user, user - with -space, space – with - the environment.